2015
DOI: 10.5194/acp-15-3021-2015
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of vertically resolved merged satellite ozone data sets: interannual variability and long-term trends

Abstract: Abstract. In the framework of the SI2N

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
114
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(123 citation statements)
references
References 69 publications
9
114
0
Order By: Relevance
“…In general, high-quality satellite-based profile ozone observations agree to within ∼ 5 % ( Fig. 2; Kramarova et al, 2013b;Tummon et al, 2015;Hubert et al, 2016). Similarly, Kramarova et al (2013b) found the drift of the higher-quality SBUV records (our Tier 1) to be within 0.5 % yr −1 when compared to independent measurements, and we see similar size drifts between the individual Tier 1 SBUV measurements, with slightly larger drifts indicated for the NOAA 16_am data at most layers.…”
Section: Monte Carlo Uncertainty Model Parameterssupporting
confidence: 70%
See 4 more Smart Citations
“…In general, high-quality satellite-based profile ozone observations agree to within ∼ 5 % ( Fig. 2; Kramarova et al, 2013b;Tummon et al, 2015;Hubert et al, 2016). Similarly, Kramarova et al (2013b) found the drift of the higher-quality SBUV records (our Tier 1) to be within 0.5 % yr −1 when compared to independent measurements, and we see similar size drifts between the individual Tier 1 SBUV measurements, with slightly larger drifts indicated for the NOAA 16_am data at most layers.…”
Section: Monte Carlo Uncertainty Model Parameterssupporting
confidence: 70%
“…The larger uncertainty associated with the linear trend parameter reflects the larger potential for merging uncertainties to alias into trends over the relatively short 2001-2015 period compared to lower potential aliasing onto the EESC functional form over the full time period. The linear trend parameter uncertainty is less than the 6 % dec −1 (2σ ) error used in the most conservative approach presented by Harris et al (2015) but greater than the uncertainty derived by Steinbrecht et al (2017) based on the spread of individual trends reported from a set of six merged ozone records. Figure 8 shows the derived trend since 2001 estimated from EESC and from a linear fit as a function of latitude for the upper-stratospheric 1.6-1.0 hPa layer.…”
Section: Multiple Linear Regression Modelmentioning
confidence: 75%
See 3 more Smart Citations